Pattern of gastrointestinal and psychosomatic symptoms across the menstrual cycle in women with inflammatory bowel disease - Erkan PARLAK,; Ülkü DAĞLI,; Canan ALKIM,; Selçuk DİŞİBEYAZ,; Bilge TUNÇ,; Aysel ÜLKER,; Burhan ŞAHİN, (Turkish Journal of Gastroenterology, 2019)
-